The burning chambers [compact disc, unabridged] - Mosse, Kate, 1961- (Mosse, Kate, 1961- Burning chambers series., 2019)
In France in 1562, a 19-year-old Minou Joubert receives an anonymous letter at her father's bookshop. Sealed with a distinctive family crest, it contains just five words: she knows that you live.